Role of Oxygen in Acetic Acid Decomposition on Pt(111) - Neitzel, Armin; Lykhach, Yaroslava; Johanek, Viktor; Tsud, Nataliya; Skala, Tomas; Prince, Kevin C.; Matolin, Vladimir; Libuda, Jörg (Journal of Physical Chemistry C, 2014)
We have investigated the role of coadsorbed atomic oxygen during the decomposition of acetic acid on Pt(111) by means of temperature-programmed desorption (TPD) and synchrotron radiation photoelectron spectroscopy (SRPES). Reaction mechanisms have been established through identification of desorbing products and surface species formed during decomposition of acetic acid, both on Pt(111) and oxygen pre-exposed p(2 X 2)-O/Pt(111). Acetate and molecularly adsorbed acetic acid are formed on both samples during the adsorption of acetic acid at 150 K. On p(2 X 2)-O/Pt(111), however, surface acetyl is identified as the principal species. The major decomposition channel for acetate and acetic acid involves formation of ketene and acetaldehyde at 222 K, and this reaction is not affected by coadsorbed oxygen. In the following reactions, partial decomposition of acetaldehyde yielded ethylene, ethylidene, ethylidyne, and small amounts of CO and methoxy on both samples. Above 222 K, decomposition of acetate on Pt(111) yields acetic acid, hydrogen, methane, and CO. In contrast, the species desorbing from p(2 X 2)-O/Pt(111) are the products of acetyl decomposition. In particular, the reaction of acetyl with atomic oxygen and surface hydroxyl groups yields methanol and acetic anhydride at 300 and 450 K, and methane and CO2 at 390 K. Decomposition of acetic acid on both Pt(111) and p(2 x 2)-O/Pt(111) results in surface carbon from decomposition of ethylidyne and partial C-C bond cleavage in the acetyl species.